9, 9′-Anthryl-anthroxyl radicals: strategic stabilization of highly reactive phenoxyl radicals. Issue 31 (13th February 2015) - Aotake, Tatsuya; Suzuki, Mitsuharu; Aratani, Naoki; Yuasa, Junpei; Kuzuhara, Daiki; Hayashi, Hironobu; Nakano, Haruyuki; Kawai, Tsuyoshi; Wu, Jishan; Yamada, Hiroko
Abstract : Stable anthroxyl radical with a half-life over 10 days in solution. Abstract : Stable 9, 9′-anthryl-anthroxyl radicals were synthesized and isolated, and the structures were fully characterized by single crystal X-ray diffraction analysis and ESR measurement. The resonance structure and steric protection of the peripheral positions and the most reactive 9-position of anthracene prolong the half-life of the radical in solution to 11 days.